The Effect of General Strength Exercises by Repetition Method on Developing Passing and Shooting Skills in Youth Football - Isam mansoor Mohin alhameed (Musamus Journal of Physical Education and Sport (MJPES), 2026)
This study aimed to identify the changes caused by Pro-Split training in certain The importance of this research lies in utilizing general strength exercises with a repetition method, based on scientifically studied foundations, to develop passing and shooting skills in youth football players, and to overcome the existing weaknesses in these skills, serving the future development of the game. The research problem is the significant deficiency in passing and shooting skills among youth players. Through the researcher’s experience, a lack of performance in these skills was observed, along with a lack of focus by some coaches on essential elements for youth players, including general muscular abilities, which are a crucial foundation for developing basic skills. Therefore, the researcher aimed to address this issue by designing general strength exercises with a repetition method to enhance these skills.The research objectives were:To prepare general strength exercises using the repetition method to develop passing and shooting skills in youth football players.To identify the statistical differences between pre-test and post-test results for the sample in passing and shooting skills The experimental method with a one-group design was used. The sample consisted of 20 youth football players (ages 14–16) from Al-Nasiriya Club in Dhi Qar Governorate. Key conclusions: The general strength exercises with a repetition method, designed by the researcher, contributed to the development of passing and shooting skills among youth football players.